Enhancing Students Motivation and Vocabulary Mastery Using Wow Mobile Game - Muhammad Asrul Hasby (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
The background of this thesis is the lack of student’s motivation to learn English vocabulary. The aim of this research was to enhance student’s motivation and vocabulary mastery using WOW Mobile game. Observation sheet, questionnaires and test was used to collect the data. The method of this research was Classroom Action Research (CAR) with 25 second grade students of MA Malaka, North Lombok and the object was Word of Wonders Mobile Game. This research was conducted in one cycle. The results of the first cycle showed that student's motivation to learn English vocabulary using the WOW mobile app reached the 8 indicators from the questionnaires and observation. Meanwhile, the result of test shown that the mean score of students was increased 3.80% (66.6 to 81.8). Based on all classroom action research activities, it can be concluded that the application of WOW mobile game as learning media can increase students' motivation to learn English vocabulary in second grade students at MA Malaka.